Proposed Legislation May Compromise Incentive to Present Unbiased Presentation of Research Data - Tereskerz, Patricia M.; Mills, Ann (Accountability in research, 2012)
Once again, Congress is considering malpractice reform through introduction of a Bill in 2011 in the House of Representatives titled: Help Efficient, Accessible, Low Cost, Timely Healthcare At of 2011 (HR5). Related proposed legislation resides in the Senate (S12) and (S218). The Act's claimed purpose is to implement reasonable, comprehensive and effective health care liability reforms. A little discussed part of this Bill which should not be allowed to remain relatively unnoticed is an embedded provision which provides immunity to manufacturers of drugs and devices from punitive damages if the drug or device is subject to U.S. Food and Drug Administration (FDA) premarket approval, clearance, or licensure by the FDA or approved, cleared, or licensed by the FDA or to those that are not FDA approved but are, generally recognized by experts as safe and effective.